Tipologi Kesejahteraan Pegawai Badan Pusat Statistik: Analisis Klaster Untuk Mendukung Kebijakan Manajemen Sumber Daya Manusia Yang Tepat Sasaran - Dede Firmansyah; Asropi Asropi (Jurnal Multidisiplin Dehasen (MUDE), 2026)
This study aims to identify the dimensions of well-being that contribute to the suboptimal level of employee welfare within Statistics Indonesia (Badan Pusat Statistik/BPS) and to formulate more targeted human resource management strategies based on employee well-being typologies. The study employs a quantitative approach using secondary data from the 2024 BPS Employee Well-Being Index, covering 35 central and provincial work units. The analysis was conducted using the K-Means Cluster method, with the optimal number of three clusters determined through hierarchical clustering and the Agglomeration Schedule. Prior to the clustering process, all variables were standardized using Z-score transformation.The results indicate that the overall level of employee well-being within BPS falls into the moderate category, with a composite index score of 72.71; however, substantial variation exists across work units. The study identifies three employee well-being typologies: low, medium, and high well-being clusters. The low well-being cluster is characterized by poor work–life balance, low job satisfaction, and unfavorable mental health conditions. The dimensions that most strongly differentiate the clusters include competency development, economic well-being, work pressure, and mental health. Based on these findings, the study recommends the implementation of cluster-based human resource policies to enhance adaptability, effectiveness, and targeting accuracy in employee well-being management.